Three-dimensional sub–100 nm resolution fluorescence microscopy of thick samples - Juette, Manuel F; Gould, Travis J; Lessard, Mark D; Mlodzianoski, Michael J; Nagpure, Bhupendra S; Bennett, Brian T; Hess, Samuel T; Bewersdorf, Joerg (Nature methods, 2008)
The ability to image thick volumes with invariant high axial and lateral resolution is a challenge for existing super-resolution fluorescence microscopy techniques. The combination of a double-plane detection scheme with fluorescence photoactivation microscopy (FPALM) allows three-dimensional sub-diffraction resolution imaging of samples as thick as whole cells. Imaging volumes as thick as whole cells at three-dimensional (3D) super-resolution is required to reveal unknown features of cellular organization. We report a light microscope that generates images with translationally invariant 30 × 30 × 75nm resolution over a depth of several micrometers. This method, named biplane (BP) FPALM, combines a double-plane detection scheme with fluorescence photoactivation localization microscopy (FPALM) enabling 3D sub-diffraction resolution without compromising speed or sensitivity.